Challenges in Diagnosing and Managing Uterus Didelphys: A Case Report - Sebastian Giovanni; Kang Heji Dian Pertiwi; Rijal, Syamsu (HM Publisher, 2024)
Background: This medical case report provides an insightful examination of a 22-year-old pregnant woman with uterus didelphys, a rare congenital anomaly of the Müllerian ducts. The introduction section sets the stage by discussing the embryological origins of congenital uterine anomalies and their varied clinical manifestations. It emphasizes the challenges in detecting these conditions due to their often asymptomatic nature and highlights their significant impact on reproductive health, including increased risks of miscarriage, preterm labor, and perinatal mortality. Case presentation: The case report segment details the patient’s clinical presentation, initially misdiagnosed as an ectopic pregnancy, later revealed to be an intrauterine pregnancy coexisting with uterus didelphys. The diagnosis was substantiated by her history of irregular menstruation, lower abdominal pain since menarche, and a previously diagnosed ovarian cyst, illustrating the critical role of a thorough medical history in guiding diagnosis. The discussion section delves into the implications of uterus didelphys on fertility and pregnancy outcomes, advocating for individualized management strategies and highlighting the psychological impact of such congenital anomalies. It underscores the necessity of a multidisciplinary approach to care involving obstetricians, radiologists, and reproductive specialists. Conclusion: The conclusion emphasizes the importance of clinical awareness, meticulous history-taking, and personalized care in the management of uterus didelphys. It calls for further research to enhance understanding and improve outcomes in reproductive medicine, stressing the complexity of diagnosing and managing pregnancies in women with Müllerian anomalies and the need to consider congenital uterine anomalies in differential diagnoses, particularly in young women with atypical gynecological histories.